Learning Styles and English Learning Achievement - Simanungkalit, Ate Gueen; Lasut, Anastasya Belinda; Rondonuwu, Joppi Jacobus (DIDASCO, 2023)
The purpose of this study was to determine the relationship between the learning styles and English achievement of a selected private Junior High School students in Manado. This research also showed the description of the student learning styles and English learning achievement. An adapted questionnaire was used to gather data from 182 student participants, wherein 55 students participated in the pilot study and 127 students participated in the actual study. The data were analyzed and interpreted with a statistical software which included the use of both descriptive and inferential statistics. The descriptive statistic showed that the students had high level of all the six learning styles and a very good level of English achievement. Analysis of inferential statistics revealed that there was no significant relationship between each of the six learning styles and English achievement. Keywords—learning style, English learning achievement Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara gaya belajar dan prestasi bahasa Inggris siswa salah satu SMP swasta yang dipilih di Manado. Penelitian ini juga menunjukkan gambaran gaya belajar siswa dan prestasi belajar bahasa Inggris. Kuesioner yang disesuaikan digunakan untuk mengumpulkan data dari 182 peserta siswa, di mana 55 siswa berpartisipasi dalam studi uji coba dan 127 siswa berpartisipasi dalam studi yang sebenarnya. Data dianalisis dan diinterpretasikan dengan perangkat lunak statistik yang meliputi penggunaan statistik deskriptif dan inferensial. Statistik deskriptif menunjukkan bahwa siswa memiliki gaya belajar yang tinggi dan tingkat pencapaian bahasa Inggris yang sangat baik. Analisis statistik inferensial mengungkapkan bahwa tidak ada hubungan yang signifikan antara masing-masing dari enam gaya belajar dan prestasi bahasa Inggris. Kata kunci—gaya belajar, prestasi belajar bahasa Inggris